Outdoor Education and its Inclusion into Teaching at PdF MU Support for the Use of Technology and the Implementation of Research Activities in the Undergraduate Education of Future Teachers - Frýzová, Iva (Masaryk University Press, 2021)
The teaching material "Outdoor Education and its Inclusion into Teaching at PdF MU. Support for the Use of Technology and the Implementation of Research Activities in the Undergraduate Education of Future Teachers" is the outcome of the project OP VVV Development of the process of undergraduate education at PdF MU: thorough preparation for good practice. One of the outcomes of the project was the preparation of innovative educational materials and courses. The courses were to reflect the educational areas within the updated Framework Educational Programme. In their content, there was to be a maximum connection of teaching with the use of cross-curricular topics. In the course of these, modern strategies for managing learning activities were to be adequately included.